Penatalaksanaan Fisioterapi Pada Kasus Pneumonia Di BBKPM Surakarta - Mahfudzoh, Siti; , Isnaini Herawati, S.Fis,S.Pd.M.Sc (2016)
Background: pneumonia is a symptom that causes disturbances of shortness of breath, increase sputum production, pain causes muscle of breath spasm, decrease of thorac expansion and decrease of functional. The modality of physiotherapy for these problem are nebulizer, infra red and chest therapy (breathing exercise, postural drainage, coughing exercise) Purpose: to study about physiotherapy management in shortness of breath, increase sputum production, pain causes muscle of breath spasm, decrease of thorac expansion and decrease of functional in the case of pneumonia using modalities nebulizer, infra red and chest therapy Results: after therapy for about four times the obtained result of the assesement of shortness of breath decreases (T0): 5 (severe) to (T4): 2 (slight). Increase sputum production (T0): sputum at upper lobus pulmo dextra and upper lobus pulmo sinitra posterior segmen with smooth ronchi (crackles), (T4): Sputum at upper lobus pulmo dextra and upper lobus pulmo sinitra posterior segmen with smooth ronchi (crackles) becomes normaly. Increased ekspansion of the thoracic cage (T0): axilla 1 cm, inter costalisV 1.5 cm and 1 cm processus xypoideus and end physiotherapy (T4): axilla 1,5 cm, inter costalis V 2 cm and 1,5 cm processus xypoideus. And also an increase in the ability of the functional activity of early physiotherapy (T0) to (T4) in leisure adapsycal category Conclusions: nebulizer, infra red and chest therapy canreduce shortness of breath, reduce pain causes spasm, reduce of sputum, increase thorac expansion, and increase functional activity